VD_FINDINFO Décision / 2013 / 149 vom 26. Dezember 2012 - VD Tribunal cantonal (2012)
INDEMNITÉEN GÉNÉRAL, AVOCAT D'OFFICE | 135 al. 2 CPP (CH), 135 al. 3 let. a CPP (CH), 135 CPP (CH), 395 let. b CPP (CH)